Pengaruh Kecemasan Isu Pemutusan Hubungan Kerja Terhadap Motivasi Kerja Karyawan PT.Gapura Angkasa di Bandar Udara Zainuddin Abdul Madjid Lombok - Vitalianti (Jurnal Multidisiplin Madani, 2022)
The success and failure of an organization in carrying out its duties and responsibilities is closely related to human resources (HR). In this study, the researchers aimed to (1) determine whether there is an influence of anxiety over the issue of termination of employment on the work motivation of PT. Gapura Angkasa employees at Zainuddin Abdul Madjid Airport, Lombok (2) To determine how much influence anxiety over the issue of termination of employment has on work motivation. employees of PT. Gapura Angkasa at Zainuddin Abdul Madjid Airport Lombok. In this study using quantitative methods with saturated sampling technique of 54 respondents employees of PT. Gapura Angkasa at Zainuddin Abdul Madjid Airport Lombok. Data analysis used simple linear regression test, t test and coefficient of determination test (R2). The results of this study indicate that, (1) the anxiety of the issue of termination of employment has a positive and significant effect on the work motivation of employees of PT. Gapura Angkasa at Zainuddin Abdul Madjid Airport Lombok. (2) the anxiety variable on the issue of termination of employment is influenced by the work motivation variable of 71.3% and the remaining 28.7% is influenced by other variables outside the variable variation model in this study.